Non-aqueous electrolyte and lithium secondary battery comprising the same
Patent Information
- Application Number
- CN202580023190.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-10-01
- Filing Date
- 2025-10-02
- Publication Date
- 2026-10-27
AI Technical Summary
[0014]本发明的非水电解质的特征在于包含由式1表示的咪唑鎓基离子液体。本发明的非水电解质可以抑制电解质和电极之间的副反应,因为由上式1表示的咪唑鎓基离子液体在负极和正极表面上形成稳定且结实的膜,从而提高包含非水电解质的锂二次电池的循环寿命。
Smart Images

Figure CN122996529A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a non-aqueous electrolyte and a lithium secondary battery containing the same. Background Technology
[0002] With the increasing interest in energy storage technology in recent years, the application of secondary batteries has expanded from small devices such as mobile phones, tablets, and laptops to medium and large electronic devices such as electric vehicles and energy storage devices. As a result, the demand for high-performance lithium secondary batteries has increased rapidly.
[0003] A lithium-ion secondary battery, comprising a negative electrode, a positive electrode, an electrolyte, and a separator, is an energy storage device in which lithium ions are repeatedly inserted into and extracted from the negative and positive electrodes disposed on the two surfaces of the separator via the electrolyte, converting and storing electrical energy as chemical energy for use. During the repeated insertion and extraction of lithium ions into and from the negative and positive electrodes, the organic solvents and lithium salts constituting the electrolyte are reduced and decomposed on the surface of the negative electrode to form a solid electrolyte interphase (SEI) composed of various organic and inorganic substances.
[0004] Here, a highly reactive electrolyte reacts with graphite used as the negative electrode or with lithium metal oxide used as the positive electrode to form compounds based on alkyl carbonates, Li₂CO₃, and Li₂O on the electrode surface. The cycle characteristics of lithium secondary batteries are greatly influenced by properties such as ionic conductivity and the mechanical properties of the films formed on the electrode surfaces. Therefore, to improve their lifespan and output characteristics, research is actively underway on additives that form stable and robust films on the negative and positive electrode surfaces to prevent side reactions between the electrolyte and electrodes and to promote smooth lithium-ion migration. Summary of the Invention
[0005] [Technical Issues]
[0006] One object of the present invention is to provide a non-aqueous electrolyte that enhances lithium-ion conductivity and suppresses electrolyte decomposition on the surface of active materials by forming a stable film on the surfaces of the positive and negative electrodes during initial charging and discharging, and achieves excellent cycling and output characteristics when applied to lithium secondary batteries.
[0007] Furthermore, another object of the present invention is to provide a lithium secondary battery comprising the aforementioned non-aqueous electrolyte.
[0008] [Technical Solution]
[0009] The present invention provides a non-aqueous electrolyte comprising a lithium salt, an organic solvent and an additive, wherein the additive comprises a compound represented by Formula 1.
[0010] [Formula 1]
[0011] In Formula 1 above, R1 is an alkenyl group having 2 to 5 carbon atoms, R2 to R4 are each independently fluorine (F) or an alkyl group having 1 to 10 carbon atoms substituted with one or more fluorine atoms, and L1 is an alkylene group having 1 to 10 carbon atoms or an aryl group having 6 to 20 carbon atoms.
[0012] Furthermore, the present invention provides a lithium secondary battery comprising a negative electrode, a positive electrode opposite to the negative electrode, a separator disposed between the negative electrode and the positive electrode, and the aforementioned non-aqueous electrolyte.
[0013] [Beneficial Effects]
[0014] The non-aqueous electrolyte of the present invention is characterized by comprising an imidazolium-based ionic liquid represented by Formula 1. The non-aqueous electrolyte of the present invention can suppress side reactions between the electrolyte and the electrodes because the imidazolium-based ionic liquid represented by Formula 1 forms a stable and robust film on the surfaces of the negative and positive electrodes, thereby improving the cycle life of the lithium secondary battery containing the non-aqueous electrolyte.
[0015] Furthermore, when using the non-aqueous electrolyte of the present invention, since the imidazolium-based ionic liquid component represented by Formula 1 reacts with the electrode before the electrolyte solvent and lithium salt, the proportion of inorganic components that improve the physical properties of the films formed on the surfaces of the negative and positive electrodes increases. As a result, the lithium-ion conductivity is improved, thereby enhancing the lifespan and high-rate characteristics of the lithium secondary battery using this non-aqueous electrolyte.
[0016] Furthermore, since the imidazolium-based ionic liquid of the present invention, represented by Formula 1, has excellent thermal stability and non-flammability due to electrostatic attraction caused by the interaction between ions in the chemical structure, it enhances the high-temperature stability of lithium secondary batteries using non-aqueous electrolytes containing imidazolium-based ionic solutions. Attached Figure Description
[0017] Figure 1 This is a schematic diagram illustrating the synthesis method of [FSPVI][TFSI] obtained in the preparation example of the present invention.
[0018] Figure 2 The FT-IR spectra of [FSPVI][TFSI] obtained in the preparation example of the present invention are shown.
[0019] Figure 3 The [FSPVI][TFSI] obtained in the preparation examples of this invention. 1 H NMR spectrum.
[0020] Figure 4 The [FSPVI][TFSI] obtained in the preparation examples of this invention.9 F NMR spectrum.
[0021] Figure 5 This is a differential charge-discharge diagram of the negative electrode half-cell using the non-aqueous electrolyte of Example 2.
[0022] Figure 6 This is a differential charge-discharge diagram of the negative electrode half-cell using the non-aqueous electrolyte of Comparative Example 1.
[0023] Figure 7 This is a differential charge-discharge diagram of the positive electrode half-cell using the non-aqueous electrolyte of Example 2.
[0024] Figure 8 This is a differential charge-discharge diagram of the positive electrode half-cell using the non-aqueous electrolyte of Comparative Example 1.
[0025] Figure 9 The graph shows the charge / discharge capacity of the lithium secondary battery prepared using the non-aqueous electrolyte of Example 2 after 300 charge / discharge cycles.
[0026] Figure 10 This is a graph showing the charge / discharge capacity of the lithium secondary battery prepared using the non-aqueous electrolyte of Comparative Example 1 after 300 charge / discharge cycles.
[0027] Figure 11 This is a graph comparing the discharge capacity of lithium secondary batteries prepared using the non-aqueous electrolytes of Examples 1 to 3 and Comparative Examples 1 to 3 after 300 charge / discharge cycles.
[0028] Figure 12 The image shows the F1s XPS spectrum of the negative electrode surface of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Example 2 after activation.
[0029] Figure 13 The image shows the S2p XPS spectrum of the negative electrode surface of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Example 2 after activation.
[0030] Figure 14 The N1s XPS spectrum is the surface of the negative electrode of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Example 2 after activation.
[0031] Figure 15 The image shows the F1s XPS spectrum of the negative electrode surface of a lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 1 after activation.
[0032] Figure 16 The S2p XPS spectrum is the surface of the negative electrode of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 1 after activation.
[0033] Figure 17The N1s XPS spectrum of the negative electrode surface of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 1 after activation is shown.
[0034] Figure 18 The image shows the F1s XPS spectrum of the positive electrode surface of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Example 2 after activation.
[0035] Figure 19 The image shows the S2p XPS spectrum of the positive electrode surface of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Example 2 after activation.
[0036] Figure 20 The N1s XPS spectrum is the positive electrode surface of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Example 2 after activation.
[0037] Figure 21 The image shows the F1s XPS spectrum of the positive electrode surface of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 1 after activation.
[0038] Figure 22 The S2p XPS spectrum is the positive electrode surface of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 1 after activation.
[0039] Figure 23 The N1s XPS spectrum of the positive electrode surface of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 1 after activation is shown.
[0040] Figure 24 This is a graph comparing the discharge capacity of lithium secondary batteries prepared using the non-aqueous electrolyte solutions of Examples 2 and Comparative Examples 1, 4 to 6 as a function of C rate.
[0041] Figure 25 This is a graph comparing the discharge capacity of a lithium secondary battery prepared using the non-aqueous electrolyte solution of Example 2 with the change of C rate.
[0042] Figure 26 This is a graph comparing the discharge capacity of a lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 1 with the C-rate.
[0043] Figure 27 This is a graph showing the change in interfacial resistance during the first cycle of lithium secondary batteries prepared using the non-aqueous electrolyte solutions of Example 2 and Comparative Example 1.
[0044] Figure 28 This is a graph showing the change in interfacial resistance during the 300th cycle of lithium secondary batteries prepared using the non-aqueous electrolyte solutions of Example 2 and Comparative Example 1.
[0045] Figure 29The image shows a SEM image of the graphite anode of a lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 1 before 300 charge / discharge cycles.
[0046] Figure 30 This is a SEM image of the graphite anode of a lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 1 after 300 charge / discharge cycles.
[0047] Figure 31 The image shows a SEM image of the graphite anode of a lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 2 before 300 charge / discharge cycles.
[0048] Figure 32 This is a SEM image of the graphite anode of a lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 2 after 300 charge / discharge cycles.
[0049] Figure 33 This is a SEM image of the NCM cathode of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 1 before 300 charge / discharge cycles.
[0050] Figure 34 This is a SEM image of the NCM cathode of a lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 1 after 300 charge / discharge cycles.
[0051] Figure 35 This is a SEM image of the NCM cathode of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Example 2 before 300 charge / discharge cycles.
[0052] Figure 36 This is a SEM image of the NCM cathode of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Example 2 after 300 charge / discharge cycles.
[0053] Figure 37 This is a graph comparing the discharge capacity of lithium secondary batteries prepared using non-aqueous electrolytes from Examples 2 and 1, 4 to 6 after 200 charge / discharge cycles. Detailed Implementation
[0054] It should be understood that the terms or words used in this specification and claims should not be construed as having the meanings defined in common dictionaries, but should be construed as having meanings and concepts consistent with the technical ideas of this disclosure, based on the inventor's ability to appropriately define the concepts of the terms to best interpret the principles of this disclosure.
[0055] It should be understood that terms such as “comprising,” “including,” or “having” as used herein are intended to indicate a particular feature, quantity, step, element, and / or combination thereof, and do not exclude the presence or addition of other particular features, quantities, steps, elements, and / or combinations thereof.
[0056] Before describing this disclosure, unless otherwise expressly stated, " "" indicates the same or different atoms or parts connected at the ends (bonding sites) of the formula.
[0057] Before describing the present invention, in the description of "a to b carbon atoms" in the specification, "a" and "b" respectively represent the number of carbon atoms contained in a specific functional group. That is, the functional group can include "a" to "b" carbon atoms. For example, "alkyl group having 1 to 5 carbon atoms" means an alkyl group containing 1 to 5 carbon atoms, namely CH3-, CH3CH2-, CH3CH2CH2-, (CH3)2CH-, CH3CH2CH2CH2-, (CH3)2CHCH2-, CH3CH2CH2CH2CH2-, (CH3)2CHCH2CH2-, etc.
[0058] Furthermore, in this specification, alkyl or aryl groups may be substituted or unsubstituted. Unless otherwise defined in the specification, the term "substitution" means that at least one hydrogen atom bonded to a carbon atom is replaced by an element other than hydrogen, such as being replaced by the following groups: alkyl having 1 to 20 carbon atoms, alkenyl having 2 to 20 carbon atoms, alkynyl having 2 to 20 carbon atoms, alkoxy having 1 to 20 carbon atoms, cycloalkyl having 3 to 12 carbon atoms, cycloalkenyl having 3 to 12 carbon atoms, cycloalkynyl having 3 to 12 carbon atoms, heterocycloalkyl having 3 to 12 carbon atoms, heterocycloalkenyl having 3 to 12 carbon atoms, heterocycloalkynyl having 2 to 12 carbon atoms, aryloxy having 6 to 12 carbon atoms, halogen atom, fluoroalkyl having 1 to 20 carbon atoms, nitro, aryl having 6 to 20 carbon atoms, heteroaryl having 2 to 20 carbon atoms, haloaryl having 6 to 20 carbon atoms, etc.
[0059] This disclosure will be described in more detail below.
[0060] Non-aqueous electrolytes
[0061] This invention relates to a non-aqueous electrolyte. More specifically, the non-aqueous electrolyte can be a non-aqueous electrolyte for lithium secondary batteries.
[0062] The non-aqueous electrolyte of the present invention is characterized by comprising a lithium salt, an organic solvent, and an additive, wherein the additive comprises a compound represented by Formula 1.
[0063] [Formula 1]
[0064] In Formula 1 above, R1 is an alkenyl group having 2 to 5 carbon atoms, R2 to R4 are each independently fluorine (F) or an alkyl group having 1 to 10 carbon atoms substituted with one or more fluorine atoms, and L1 is an alkylene group having 1 to 10 carbon atoms or an aryl group having 6 to 20 carbon atoms.
[0065] The non-aqueous electrolyte of the present invention can suppress side reactions between the electrolyte and the electrode because the additive containing imidazolium-based ionic liquid forms a stable and robust film on the negative and positive electrode surfaces, and the proportion of inorganic components that improve the physical properties of the film formed on the negative and positive electrode surfaces and enhance the conductivity of lithium ions can be increased, thereby enhancing lifespan and high-temperature characteristics, including the cycle life of lithium secondary batteries containing non-aqueous electrolytes.
[0066] (1) Lithium salts
[0067] As the lithium salt used in this invention, various lithium salts commonly used in electrolytes for lithium secondary batteries can be used without limitation. For example, the lithium salt may contain Li + As a cation, and may contain a selection from F - Cl - ,Br - I - NO3 - N(CN)2 - BF4 - ClO4 - AlO4 - AlCl4 - PF6 - SbF6 - AsF6 - B 10 Cl 10 - BF2C2O4 - BC4O8 - PF4C2O4 - PF2C4O8 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - CF3SO3 - C4F9SO3 - CF3CF2SO3 - (FSO2)2N -CF3CF2(CF3)2CO - (CF3SO2)2CH - CH3SO3 - CF3(CF2)7SO3 - CF3CO2 - CH3CO2 - SCN - and (CF3CF2SO2)2N - At least one of them is used as an anion.
[0068] Specifically, lithium salts may include those selected from lithium chloride (LiCl), lithium bromide (LiB), lithium iodide (LiI), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium tetraoxaluminate (LiAlO4), lithium tetrachloroaluminate (LiAlCl4), lithium hexafluorophosphate (LiPF6), lithium hexafluoroantimonyrate (LiSbF6), lithium hexafluoroarsenate (LiAsF6), and lithium decachlorodecanoate (LiB). 10 Cl 10 The lithium salt may include at least one of lithium bis(oxalatoborate) (LiBOB(LiB(C2O4)2)), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(fluorosulfonyl)imide (LiFSI(LiN(SO2F)2)), lithium methanesulfonate (LiCH3SO3), lithium trifluoroacetate (LiCF3CO2), lithium acetate (LiCH3CO2), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2F)2), and lithium bis(perfluoroethylsulfonyl)imide (LiBETI(LiN(SO2CF2CF3)2)). Specifically, the lithium salt may include at least one selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2F)2), lithium perchlorate (LiClO4), and lithium bis(oxalatoborate) (LiBOB(LiB(C2O4)2)).
[0069] The concentration of lithium salt in the non-aqueous electrolyte can range from 0.5 M to 5.0 M, specifically from 0.8 M to 4.0 M, and more specifically from 0.8 M to 2.0 M. When the lithium salt concentration meets the above range, this can improve the performance of Li... + This improves the battery's output characteristics by increasing the transport number and the degree of lithium-ion dissociation.
[0070] (2) Organic solvents
[0071] Organic solvents are commonly used non-aqueous solvents in lithium secondary batteries, and there are no restrictions, as long as they can minimize the decomposition caused by oxidation reactions during battery charging and discharging.
[0072] Specifically, the organic solvent may include at least one organic solvent selected from cyclic carbonate organic solvents, linear carbonate organic solvents, linear ester organic solvents, and cyclic ester organic solvents.
[0073] Cyclic carbonate organic solvents are organic solvents with high viscosity and high dielectric constant, and are therefore organic solvents that can effectively dissociate lithium salts in electrolytes. Specifically, they may include at least one organic solvent selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentene carbonate, 2,3-pentene carbonate and vinylene carbonate, and more specifically, ethylene carbonate.
[0074] In addition, linear carbonate organic solvents are organic solvents with low viscosity and low dielectric constant. Specifically, they may include at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate and ethyl propyl carbonate, and more specifically, they may include ethyl methyl carbonate (EMC).
[0075] Specifically, the organic solvent can be a mixture of cyclic carbonate organic solvents and linear carbonate organic solvents. The cyclic carbonate organic solvents and linear carbonate organic solvents can be mixed in a volume ratio of 10:90 to 40:60, specifically 10:90 to 30:70, and more specifically 15:85 to 30:70. If the mixing ratio of the cyclic carbonate organic solvents to the linear carbonate organic solvents meets the above ranges, both high dielectric constant and low viscosity characteristics can be achieved, resulting in excellent ionic conductivity characteristics.
[0076] In addition, in order to prepare an electrolyte with high ionic conductivity, in addition to at least one carbonate organic solvent selected from cyclic carbonate organic solvents and straight-chain carbonate organic solvents, the organic solvent may also contain at least one ester organic solvent selected from straight-chain ester organic solvents and cyclic ester organic solvents.
[0077] Straight-chain ester organic solvents may include at least one selected from methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate.
[0078] In addition, cyclic ester organic solvents may contain at least one selected from γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.
[0079] Furthermore, organic solvents commonly used for non-aqueous electrolytes can be added as needed without limitation. For example, it may further comprise at least one organic solvent selected from ether organic solvents, glycol diether solvents, and nitrile organic solvents.
[0080] As an ether solvent, any one or a mixture of two or more of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, 1,3-dioxolane (DOL) and 2,2-bis(trifluoromethyl)-1,3-dioxolane (TFDOL) can be used, but not limited thereto.
[0081] Compared to linear carbonate organic solvents, glycol diether solvents have high dielectric constants and low surface tensions, and may include, but are not limited to, at least one selected from dimethoxyethane (glycol dimethyl ether, DME), diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether (TEGDME) as a solvent with low reactivity with metals.
[0082] Nitrile solvents may include, but are not limited to, at least one selected from acetonitrile, propionitrile, butyronitrile, valerate, octanoic acid, heptanonitrile, cyclopentanoic acid, cyclohexanoic acid, 2-fluorobenzyl nitrile, 4-fluorobenzyl nitrile, difluorobenzyl nitrile, trifluorobenzyl nitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile.
[0083] (3) Additives
[0084] The non-aqueous electrolyte of the present invention includes additives. Specifically, the additives include compounds represented by Formula 1.
[0085] [Formula 1]
[0086] In Formula 1 above, R1 is an alkenyl group having 2 to 5 carbon atoms, R2 to R4 are each independently fluorine (F) or an alkyl group having 1 to 10 carbon atoms substituted with one or more fluorine atoms, and L1 is an alkylene group having 1 to 10 carbon atoms or an aryl group having 6 to 20 carbon atoms.
[0087] Specifically, in Formula 1 above, R1 can be an alkenyl group having 2 to 5 carbon atoms, more specifically an alkenyl group having 2 to 4 carbon atoms, more specifically an alkenyl group having 2 to 3 carbon atoms, and even more specifically a vinyl group. An alkenyl group having 2 to 4 carbon atoms can be, for example, Formula R1-1, Formula R1-2, or Formula R1-3, and more specifically, Formula R1-1.
[0088] [Equation R1-1]
[0089] [Equation R1-2]
[0090] [Equation R1-3]
[0091] R2 through R4 can be independently fluorine or substituted with one or more fluorine-containing alkyl groups having 1 to 10 carbon atoms, specifically fluorine or substituted with one or more fluorine-containing alkyl groups having 1 to 6 carbon atoms, more specifically fluorine or fully substituted with one or more fluorine-containing alkyl groups having 1 to 4 carbon atoms, and even more specifically fluorine or trifluoromethyl. Even more specifically, R2 can be fluorine. Furthermore, R3 and R4 can each be trifluoromethyl.
[0092] L1 can be an alkylene group having 1 to 10 carbon atoms or an arylene group having 6 to 20 carbon atoms, specifically an alkylene group having 1 to 5 carbon atoms or an arylene group having 6 to 20 carbon atoms, more specifically an alkylene group having 1 to 3 carbon atoms or an arylene group having 6 to 15 carbon atoms, more specifically an alkylene group having 1 to 3 carbon atoms or an arylene group having 6 to 10 carbon atoms, more specifically an arylene group having 6 to 10 carbon atoms, and even more specifically a phenylene group. The phenylene group can be, for example, of the following formulas L1-1, L1-2, or L1-3, and more specifically, of formula L1-1.
[0093] [Formula L1-1]
[0094] [Formula L1-2]
[0095] [Formula L1-3]
[0096] The compound represented by Formula 1 is an imidazolium-based ionic liquid in which cations and anions are bonded by electro-attraction, and it exhibits high thermal stability, electrical conductivity, and non-flammability. Furthermore, due to its imidazolium ring structure, it exhibits a resonance stabilization effect and is not easily deformed or decomposed even at high temperatures.
[0097] Furthermore, because R1 has a highly reactive carbon-carbon double bond, it reacts with the negative and positive electrodes, respectively, during the initial charging and discharging process, before the electrolyte solvent and lithium salt, to form SEI and CEI.
[0098] L1 is an alkylene group having 1 to 10 carbon atoms or an aryl group having 6 to 20 carbon atoms, which helps to enhance the physical properties of the formed film when the additive of the present invention forms a film in the positive and negative electrodes.
[0099] In Equation 1 above, R2 to R4 are each independently fluorine or alkyl groups having 1 to 10 carbon atoms substituted with one or more fluorine atoms, which helps to form uniform and thin films for both the negative and positive electrodes. As a result, lithium-ion mobility is improved. Specifically, when the SEI layer is formed, fluorine-containing compounds produce stable components such as lithium fluoride (LiF), making the SEI layer more uniform and thinner, and the high electronegativity of fluorine reduces the solvation energy of lithium ions in the solvation structure of lithium ions, thereby allowing lithium ions to move more freely.
[0100] Therefore, the use of non-aqueous electrolyte in this invention can enhance the physical properties of the membrane, suppress the reduction in battery capacity caused by the loss of electrolyte solvent and lithium salt, and enhance the lithium ion mobility at the electrode interface.
[0101] Specifically, the compounds represented by Formula 1 may include compounds represented by Formula 1-1 below.
[0102] [Equation 1-1]
[0103] When the compound represented by Formula 1-1, namely bis(trifluoromethanesulfonyl)imide 3-(4-fluorophenyl)sulfonyl-1-vinyl-imidazolium (which can be represented by [FSPVI][TFSI] herein), is included in the electrolyte of a lithium secondary battery, side reactions between the electrolyte and electrodes due to the formation of stable and robust films on the positive and negative electrode surfaces are suppressed, and lithium-ion conductivity is improved more smoothly. Considering that the core effects of improving the lifespan and output characteristics of the lithium secondary battery of the present invention can be achieved more superiorly, the use of the compound represented by Formula 1-1 as an additive is preferred.
[0104] The content of the compound represented by Formula 1 in the non-aqueous electrolyte can be 0.15% by weight or more, 0.2% by weight or more, 0.3% by weight or more, 0.4% by weight or more, or 0.5% by weight or more. The content of the compound represented by Formula 1 can be less than 20% by weight, less than 15% by weight, less than 12% by weight, less than 10% by weight, less than 8% by weight, less than 5% by weight, less than 3% by weight, less than 2% by weight, less than 1.5% by weight, less than 1% by weight, or less than 0.8% by weight. The above ranges can be combined without limitation.
[0105] More specifically, the content of the compound represented by Formula 1 in the non-aqueous electrolyte can be from 0.15 wt% to 10 wt%, specifically from 0.2 wt% to 5 wt%, more specifically from 0.2 wt% to 3 wt%, even more specifically from 0.3 wt% to 2 wt%, even more specifically from 0.4 wt% to 1 wt%, and even more specifically from 0.4 wt% to 0.8 wt%. When the content of the compound represented by Formula 1 meets the above range, a stable film is formed on the positive and negative electrodes, thereby improving cycle life.
[0106] In addition to the compounds represented by Formula 1, the additives of the present invention may also include other additives. These additional additives may be included in the non-aqueous electrolyte to prevent decomposition of the non-aqueous electrolyte under high-output conditions, which could lead to negative electrode collapse, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, overcharge protection, and battery swelling suppression at high temperatures. Even when using co-additives that further contain additional additives beyond the compounds represented by Formula 1 of the present invention, there are no adverse effects, and they exhibit superior performance in improving cycle performance compared to using the compounds represented by Formula 1 alone in the same amount.
[0107] Specifically, the additional additives may further include at least one selected from vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, propane sulpholactone, propylene sulpholactone, butane sulpholactone, biphenyl, divinyl sulfone, succinic acid, adiponitrile, ethylene sulfate, ethylene sulfite, propylene sulfite, diallyl sulfonate, lithium difluorooxalate borate (LiODFB), lithium bis(oxalate)borate (LiBOB), tris(trimethylsilyl) phosphate (TMSPa), and tris(trimethylsilyl) phosphite (TMSPi), and may further include at least one selected from vinylene carbonate and propane sulpholactone, and more specifically may include vinylene carbonate.
[0108] Specifically, the content of additional additives in the non-aqueous electrolyte can be from 0.1% to 10% by weight, specifically from 0.1% to 5.0% by weight, more specifically from 0.1% to 2.0% by weight, and even more specifically from 0.1% to 0.9% by weight.
[0109] Lithium secondary batteries
[0110] In addition, the present invention provides a lithium secondary battery comprising the above-mentioned non-aqueous electrolyte.
[0111] Specifically, a lithium secondary battery includes a positive electrode, a negative electrode opposite to the positive electrode, a separator disposed between the positive and negative electrodes, and the aforementioned non-aqueous electrolyte.
[0112] At this time, the lithium secondary battery of the present invention can be manufactured by conventional methods known in the art. For example, the lithium secondary battery of the present invention can be manufactured by forming an electrode assembly in which a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode are sequentially stacked, then inserting the electrode assembly into a battery case, and then injecting the non-aqueous electrolyte of the present invention thereinto.
[0113] (1) Positive Electrode
[0114] The positive electrode may include a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector.
[0115] The positive electrode current collector is not particularly limited as long as it has high electrical conductivity without causing adverse chemical changes in the battery. Specifically, the positive electrode current collector may include at least one selected from copper, stainless steel, aluminum, nickel, titanium, sintered carbon, and aluminum-cadmium alloy, and preferably may include aluminum.
[0116] The positive electrode current collector generally has a thickness of 3 μm to 500 μm.
[0117] Microscopic irregularities may be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. For example, the positive electrode current collector may be used in various shapes such as a film, a sheet, a foil, a mesh, a porous body, a foam body, and a non-woven fabric body, etc.
[0118] The positive electrode active material layer may be disposed on at least one surface of the positive electrode current collector. Specifically, the positive electrode active material layer may be disposed on one or both surfaces of the positive electrode current collector.
[0119] The positive electrode active material layer may include a positive electrode active material.
[0120] The positive electrode active material is a compound capable of reversibly intercalating and deintercalating lithium, wherein the positive electrode active material may include a lithium transition metal composite oxide that includes lithium and at least one transition metal selected from nickel, cobalt, manganese, and aluminum, and may preferably include a lithium transition metal composite oxide that includes lithium and transition metals including nickel, cobalt, and manganese.
[0121] For example, the lithium transition metal composite oxide may include lithium manganese-based oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium cobalt-based oxides (e.g., LiCoO2, etc.), lithium nickel-based oxides (e.g., LiNiO2, etc.), lithium nickel manganese-based oxides (e.g., LiNi 1-Y Mn
[0113] O2 (where 0<Y<1), LiMn 2-z Ni z O4 (where 0<Z<2), etc.), lithium nickel cobalt-based oxides (e.g., LiNi Y1 Co Y1 O₂(where 0<Y1<1), etc.), lithium manganese cobalt-based oxides (e.g., LiCo 1-Y2 Mn Y2 O₂(where 0<Y2<1), LiMn 2- z1 Co z1 O₄(where 0<Z1<2), etc.), lithium nickel manganese cobalt-based oxides (e.g., Li(Ni p Co q Mn r1 )O₂(where 0<p<1, 0<q<1, 0<r1<1 and p+q+r1=1) or Li(Ni p1 Co q1 Mn r2 )O₄(where 0<p1<2, 0<q1<2, 0<r2<2 and p1+q1+r2=2) or lithium-nickel-cobalt-transition metal (M) oxides (e.g., Li(Ni p2 Co q2 Mn r3 M s2 )O₂(where M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg and Mo, and p2, q2, r3 and s2 are the atomic fractions of the respective independent elements, where 0<p2<1, 0<q2<1, 0<r3<1, 0<s2<1 and p2+q2+r3+s2=1), etc.), and may include any one or a combination of two or more of these compounds. Among these materials, from the viewpoint of being able to improve the capacity characteristics and stability of the battery, the lithium transition metal composite oxide may be LiCoO₂, LiMnO₂, LiNiO₂, lithium nickel manganese cobalt oxides (e.g., Li(Ni 0.6 Mn 0.2 Co 0.2 )O₂, Li(Ni 0.5 Mn 0.3 Co 0.2 )O₂, Li(Ni 0.7 Mn 0.15 Co 0.15 )O₂ or Li(Ni 0.8 Mn 0.1 Co 0.1 )O₂, etc.), lithium nickel cobalt aluminum oxides (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 )O₂, etc.), and the like, in consideration of the significant improvement effect produced by controlling the types and content ratios of the constituent elements forming the lithium transition metal composite oxide, the lithium transition metal composite oxide may be Li(Ni 0.6 Mn 0.2 Co0.2 )O₂, Li(Ni 0.5 Mn 0.3 Co 0.2 )O₂, Li(Ni 0.7 Mn 0.15 Co 0.15 )O₂ or Li(Ni 0.8 Mn 0.1 Co 0.1 )O₂ and the like, and any one of them or a mixture of two or more thereof may be used.
[0122] More specifically, the positive electrode active material may be a lithium transition metal composite oxide, and may contain 60 mol% or more of nickel based on the total number of moles of transition metals contained in the lithium transition metal composite oxide. Specifically, the positive electrode active material is a lithium transition metal composite oxide, the transition metal comprises nickel and at least one selected from manganese, cobalt or aluminum, and based on the total number of moles of the transition metal, the content of nickel may be 60 mol% or more, specifically 60 mol% to 90 mol%. When such a lithium transition metal composite oxide with a high nickel content is used together with the above non-aqueous electrolyte, it is preferable from the viewpoint of reducing gaseous by-products generated due to structural destruction.
[0123] In addition, the positive electrode active material may include a lithium composite transition metal oxide represented by the following Formula 2.
[0124] [Formula 2]
[0125] Li 1+x (Ni a Co b Mn c M d )O₂
[0126] In Formula 2, M is at least one selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, 1+x, a, b, c and d are each independent atomic fraction of the element, where 0≤x≤0.2, 0.50≤a<1, 0<b≤0.25, 0<c≤0.25, 0≤d≤0.1 and a+b+c+d=1.
[0127] Preferably, a, b, c and d may be 0.70≤a≤0.95, 0.025≤b≤0.20, 0.025≤c≤0.20 and 0≤d≤0.05, respectively.
[0128] Preferably, a, b, c and d may be 0.80≤a≤0.95, 0.025≤b≤0.15, 0.025≤c≤0.15 and 0≤d≤0.05, respectively.
[0129] Preferably, a, b, c, and d can be 0.85≤a≤0.90, 0.05≤b≤0.10, 0.05≤c≤0.10, and 0≤d≤0.03, respectively.
[0130] In addition to the aforementioned positive electrode active material, the positive electrode active material layer may further include a binder and / or a conductive agent.
[0131] The adhesive is a component that facilitates the bonding of the active material with the conductive material and with the current collector. Specifically, it may include at least one selected from polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, and fluororubber, preferably polyvinylidene fluoride.
[0132] From the perspective of ensuring sufficient bonding force between components such as positive electrode active material, the content of binder in the positive electrode active material layer can be from 1% to 20% by weight, preferably from 1.2% to 10% by weight.
[0133] To ensure sufficient cohesion between components such as the positive electrode active material, the positive electrode active material may be included in the positive electrode active material layer in an amount of 1% to 20% by weight, preferably 1.2% to 10% by weight.
[0134] Conductive agents can be used to assist and improve the conductivity in secondary batteries, and there are no particular limitations, as long as they are conductive and do not cause chemical changes. Specifically, the positive electrode conductive agent may include at least one selected from the following: graphite, such as natural or artificial graphite; carbon black, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermally cracked carbon black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; fluorocarbons; metal powders, such as aluminum and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives. Preferably, the conductive agent may include carbon black to improve conductivity.
[0135] To ensure sufficient conductivity, the content of the conductive agent in the positive electrode active material layer can be from 1% to 20% by weight, preferably from 1.2% to 10% by weight.
[0136] The thickness of the positive electrode active material layer can be from 30 μm to 400 μm, preferably from 40 μm to 110 μm.
[0137] The positive electrode can be manufactured by coating a positive electrode current collector with a positive electrode slurry containing positive electrode active material and optional binder, conductive material and solvent for forming positive electrode slurry, followed by drying and rolling.
[0138] The solvent used to form the cathode slurry may include an organic solvent, such as N-methyl-2-pyrrolidone (NMP). The solids content of the cathode slurry may be from 40% to 90% by weight, specifically from 50% to 80% by weight.
[0139] (2) Negative electrode
[0140] The negative electrode is opposite to the positive electrode.
[0141] The negative electrode may include a negative electrode current collector and a layer of negative electrode active material disposed on at least one surface of the negative electrode current collector.
[0142] There are no particular restrictions on the negative electrode current collector, as long as it has high conductivity and will not cause adverse chemical changes in the battery. Specifically, the negative electrode current collector can be made of copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel with a surface treatment of carbon, nickel, titanium, silver, etc., or aluminum-cadmium alloys.
[0143] The thickness of the negative electrode current collector can range from 3 μm to 500 μm.
[0144] The negative electrode current collector can form tiny bumps and depressions on its surface to improve the adhesion of the negative electrode active material. For example, the negative electrode current collector can be used in various shapes such as membrane, sheet, foil, mesh, porous body, foam, non-woven body, etc.
[0145] The negative electrode active material layer is disposed on at least one surface of the negative electrode current collector. Specifically, the negative electrode active material layer may be disposed on one or both surfaces of the negative electrode current collector.
[0146] The negative electrode active material layer may contain negative electrode active material.
[0147] The negative electrode active material is a compound capable of reversibly inserting and deintercalating lithium ions, and may include at least one selected from the group consisting of carbon-based active materials, (semi-)metal active materials, and lithium metal, and specifically may include at least one selected from the group consisting of carbon-based active materials and (semi-)metal active materials. Furthermore, the negative electrode active material may include carbon-based active materials and (semi-)metal active materials.
[0148] Carbon-based active materials may include at least one selected from graphite, hard carbon, soft carbon, carbon black, graphene, and fibrous carbon, and preferably may include graphite.
[0149] In terms of ensuring structural stability during charging and discharging and reducing side reactions with the electrolyte solution, the average particle size (D) of carbon-based active materials is crucial. 50 The diameter can be from 10 μm to 30 μm, preferably from 15 μm to 25 μm.
[0150] Specifically, (semi)metal active materials may include: at least one selected from Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, V, Ti, and Sn; alloys of lithium and metals selected from Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, V, Ti, and Sn; oxides of at least one (semi)metal selected from Cu, Ni, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, V, Ti, and Sn; lithium titanium oxide (LTO); lithium vanadium oxide; and so on.
[0151] More specifically, (semi)metal active materials may include silicon-based active materials.
[0152] Silicon-based active materials may include those made of SiO2 X Compounds represented by (0≤x<2). In the case of SiO2, since it cannot be stored because it does not react with lithium ions, x is preferably within the above range. More preferably, the silicon-based active material can be SiO.
[0153] In terms of ensuring structural stability during charging and discharging and reducing side reactions with the electrolyte solution, the average particle size (D) of silicon-based active materials is crucial. 50 The diameter can range from 1 μm to 30 μm, preferably from 2 μm to 15 μm.
[0154] The content of negative electrode active material in the negative electrode active material layer can be from 60% to 99% by weight, specifically from 75% to 98% by weight.
[0155] In addition to the aforementioned negative electrode active material, the negative electrode active material layer may also contain adhesives and / or conductive materials.
[0156] The adhesive is used to improve battery performance by improving the adhesion between the negative electrode active material layer and the negative electrode current collector. For example, it may include at least one selected from polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, and materials wherein hydrogen is substituted by Li, Na, or Ca, and may also include various copolymers thereof.
[0157] The binder content can be from 0.5% to 10% by weight, depending on the total weight of the negative electrode active material layer.
[0158] Any conductive material can be used without particular restriction, as long as it is conductive and does not cause adverse chemical changes in the battery. Examples of conductive materials that can be used include: graphite, such as natural or artificial graphite; carbon black, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermally cracked carbon black; conductive fibers, such as carbon fibers or metal fibers; conductive tubes, such as carbon nanotubes; fluorocarbons; metal powders, such as aluminum and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; polyphenylene derivatives, etc.
[0159] The content of conductive material in the negative electrode active material layer can be from 0.5% to 10% by weight, specifically from 1% to 7% by weight.
[0160] The thickness of the negative electrode active material layer can be from 10 μm to 100 μm.
[0161] The negative electrode can be manufactured by coating a negative electrode current collector with a negative electrode slurry containing a negative electrode active material and optional binder, conductive material and solvent for forming the negative electrode slurry, followed by drying and rolling.
[0162] The solvent used to form the negative electrode slurry may include, for example, at least one selected from distilled water, N-methyl-2-pyrrolidone (NMP), ethanol, methanol, and isopropanol, and distilled water is preferred to promote the dispersion of the negative electrode active material, binder, and / or conductive material. The solids content of the negative electrode slurry may be from 30% to 80% by weight, and specifically from 40% to 70% by weight.
[0163] (3) Diaphragm
[0164] Furthermore, as a separator, porous polymer membranes commonly used as separators can be used alone or in combination, such as porous polymer membranes prepared from polyolefin polymers like ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers. Alternatively, typical porous nonwoven fabrics can be used, such as nonwoven fabrics formed from high-melting-point glass fibers or polyethylene terephthalate fibers, but the invention is not limited thereto. To ensure heat resistance or mechanical strength, coated separators containing ceramic components or polymer materials can also be used, and can be selectively used in single-layer or multi-layer structures.
[0165] The shape of the lithium secondary battery of the present invention is not particularly limited, and it can be cylindrical, prismatic, pouch or coin-shaped.
[0166] [Embodiments of the Invention]
[0167] The invention will be described in detail below with reference to embodiments. However, the invention can be embodied in many different forms and should not be construed as limited to the embodiments set forth herein. It will be apparent to those skilled in the art that various modifications and alterations can be made without departing from the scope and spirit of the invention, and such modifications and alterations are of course included within the invention as defined by the appended claims.
[0168] Examples and Comparative Examples
[0169] Preparation Example: Synthesis of bis(trifluoromethylsulfonyl)imine 3-((4-fluorophenyl)sulfonyl)-1-vinyl-imidazolium ([FSPVI][TFSI])
[0170] (1) Step 1: Synthesis of bis(trifluoromethylsulfonyl)imine 3-((4-fluorophenyl)sulfonyl)-1-vinyl-imidazolium ([FSPVI][TFSI])
[0171] Figure 1 This is a schematic diagram illustrating the method for synthesizing 3-(4-(fluorophenyl)sulfonyl)-1-vinyl-1H-imidazol-3-onium chloride [FSPVI][Cl] from 1-vinylimidazolium and 4-fluorobenzenesulfonyl chloride. First, the reactants given in Table 1 were dissolved in dichloromethane (DCM) solvent and placed in a double-jacketed reactor. After placing all reactants in a reactor at 25°C, the reaction proceeded for 6 hours. The resulting compound was precipitated using an ether solvent and then dried under vacuum at 40°C for 12 hours to give 3-(4-(fluorophenyl)sulfonyl)-1-vinyl-1H-imidazol-3-onium chloride ([FSPVI][Cl]), and then... Figure 2 Its structure was confirmed by FT-IR spectroscopy.
[0172] [Table 1]
[0173] (2) Step 2: Synthesis of bis(trifluoromethylsulfonyl)imine 3-((4-fluorophenyl)sulfonyl)-1-vinyl-imidazolium ([FSPVI][TFSI])
[0174] exist Figure 1 Step 2 provides a schematic diagram of the synthesis of bis(trifluoromethanesulfonyl)imine 3-((4-fluorophenyl)sulfonyl)-1-vinyl-imidazolium ([FSPVI][TFSI]). First, the reactants given in Table 2 were dissolved in deionized water (DI) solvent and placed in a double-jacketed reactor. After placing all reactants in a reactor at 25°C, the reaction proceeded for 2 hours. Distilled water was removed from the resulting solution, and byproducts were removed by phase separation using water and dichloromethane solvent. The final product synthesized by the above method was vacuum dried at 40°C for 24 hours, and then... Figure 2 FT-IR spectra and Figure 3 of 1 H NMR spectra and Figure 4 of 19 F NMR spectroscopy confirmed the chemical structure.
[0175] 1 H NMR (DMSO), δ (ppm): 9.41 (s, 1H), 8.19 (s, 1H), 7.81 (s, 1H), 7.63 (m, 2H), 7.31 (m, 1H), 7.13 (t, 2H), 5.97 (m, 1H), 5.4 (m, 1H)
[0176] 19 F NMR (DMSO), δ (ppm): -78.8 (s), -113.3 (m)
[0177] [Table 2]
[0178] Comparative Example 1: Non-aqueous electrolyte prepared by mixing lithium salt and organic solvent
[0179] The non-aqueous electrolyte of Comparative Example 1 was prepared by adding lithium hexafluorophosphate (LiPF6) salt at a concentration of 1 M to a mixed solvent of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) (volume ratio: 30 / 70).
[0180] Comparative Example 2
[0181] The non-aqueous electrolyte of Comparative Example 2 was prepared by adding bis(trifluoromethylsulfonyl)imide 3-((4-fluorophenyl)sulfonyl)-1-vinyl-imidazolium ([FSPVI][TFSI]) obtained in the preparation example to the non-aqueous electrolyte of Comparative Example 1, such that its content reached 0.1% by weight based on the total weight of the non-aqueous electrolyte.
[0182] Comparative Example 3
[0183] The non-aqueous electrolyte of Comparative Example 3 was prepared by adding bis(trifluoromethylsulfonyl)imide 3-((4-fluorophenyl)sulfonyl)-1-vinyl-imidazolium ([FSPVI][TFSI]) obtained in the preparation example to the non-aqueous electrolyte of Comparative Example 1, such that its content reached 5.0% by weight based on the total weight of the non-aqueous electrolyte.
[0184] Comparative Example 4
[0185] The non-aqueous electrolyte of Comparative Example 4 was prepared by adding the compound represented by Formula 3 to the non-aqueous electrolyte of Comparative Example 1, such that its content reached 0.5% by weight based on the total weight of the non-aqueous electrolyte.
[0186] [Formula 3]
[0187] Comparative Example 5
[0188] The non-aqueous electrolyte of Comparative Example 5 was prepared by adding the compound represented by Formula 4 to the non-aqueous electrolyte of Comparative Example 1, such that its content reached 0.5% by weight based on the total weight of the non-aqueous electrolyte.
[0189] [Formula 4]
[0190] Comparative Example 6
[0191] The non-aqueous electrolyte of Comparative Example 6 was prepared by adding the compound represented by Formula 5 to the non-aqueous electrolyte of Comparative Example 1, such that its content reached 0.5% by weight based on the total weight of the non-aqueous electrolyte.
[0192] [Formula 5]
[0193] Example 1
[0194] The non-aqueous electrolyte was prepared by adding bis(trifluoromethylsulfonyl)imine 3-((4-fluorophenyl)sulfonyl)-1-vinyl-imidazolium ([FSPVI][TFSI]) obtained in the preparation example to the non-aqueous electrolyte of Comparative Example 1, such that its content reached 0.2% by weight based on the total weight of the non-aqueous electrolyte.
[0195] Example 2
[0196] The non-aqueous electrolyte was prepared by adding bis(trifluoromethylsulfonyl)imide 3-((4-fluorophenyl)sulfonyl)-1-vinyl-imidazolium ([FSPVI][TFSI]) obtained in the preparation example to the non-aqueous electrolyte of Comparative Example 1, such that its content reached 0.5% by weight based on the total weight of the non-aqueous electrolyte.
[0197] Example 3
[0198] The non-aqueous electrolyte was prepared by adding bis(trifluoromethylsulfonyl)imine 3-((4-fluorophenyl)sulfonyl)-1-vinyl-imidazolium ([FSPVI][TFSI]) obtained in the preparation example to the non-aqueous electrolyte of Comparative Example 1, such that its content reached 3.0% by weight based on the total weight of the non-aqueous electrolyte.
[0199] Experimental Example
[0200] Experimental Example 1: Evaluation of Electrochemical Properties
[0201] The electrochemical properties of the non-aqueous electrolytes prepared in Example 2 and Comparative Example 1 were evaluated. Figure 5 This is a differential charge / discharge diagram of the negative electrode half-cell using the non-aqueous electrolyte of Example 2. Figure 6 This is a differential charge / discharge diagram of the negative electrode half-cell using the non-aqueous electrolyte of Comparative Example 1. Specifically, Figure 5 and 6 This is a graph showing the voltage (V) on the X-axis and the value (dQ / dV) obtained by differentiating the battery capacity (Q) with the voltage (V) by applying a current corresponding to 0.01C to a negative electrode half-cell with a graphite negative electrode as the working electrode and lithium metal as the reference electrode to charge the negative electrode half-cell to 0.01V. Figure 7 This is a differential charge / discharge diagram of the positive electrode half-cell using the non-aqueous electrolyte of Example 2. Figure 8 This is a differential charge / discharge diagram of the positive electrode half-cell using the non-aqueous electrolyte of Comparative Example 1. Specifically, Figure 7 and Figure 8 This illustrates the application of a current corresponding to 0.01 C to a substrate including LiNi. 0.8 Co 0.1 Mn 0.1 Using O2 (hereinafter referred to as NCM811) as the positive electrode active material, and lithium metal as the reference electrode, the positive electrode is charged to 4.3V. The X-axis represents the voltage (V), and the Y-axis represents the curve of the value (dQ / dV) obtained by differentiating the battery capacity (Q) with respect to the voltage (V).
[0202] and Figure 6 Different, for Figure 5 The non-aqueous electrolyte of Example 2 exhibited a new reduction peak in the 1.3 V region, which was caused by the reduction reaction of the imidazolium-based ionic liquid ([FSPVI][TFSI]) additive. Furthermore, with... Figure 8 Different, for Figure 7 In the non-aqueous electrolyte of Example 2, a new oxidation peak was observed in the 3.58 V region, which was caused by the oxidation reaction of the imidazolium-based ionic liquid ([FSPVI][TFSI]) additive. These results confirm that when the imidazolium-based ionic liquid ([FSPVI][TFSI]) additive of the present invention is applied to the electrolyte, a film can be formed on the positive and negative electrode surfaces through reduction and oxidation reactions.
[0203] Experiment Example 2: Evaluation of Cyclic Characteristics
[0204] (Preparation of lithium secondary batteries)
[0205] Graphite anode active material, PVDF (polyvinylidene fluoride) binder, and Super P conductive material were mixed in a weight ratio of 90:3:7, and the mixture was dispersed in N-methyl-2-pyrrolidone (NMP) solvent by stirring for more than 12 hours to prepare anode slurry. The prepared anode slurry was coated with a 15 μm thick copper current collector, and then vacuum dried at 100°C for more than 12 hours to remove residual solvent and moisture. A cathode active material (LiNi) with a Ni content of 80% was then used. 0.8 Co 0.1 Mn 0.1 O2 (hereinafter referred to as NCM 811), PVDF binder, and Super P conductive material were mixed in a weight ratio of 95:3:2, and the mixture was dispersed in NMP solvent by stirring for more than 12 hours to prepare a positive electrode slurry. The prepared NCM 811 slurry was coated with an aluminum current collector with a thickness of 15 μm, and then vacuum dried at 80°C for 12 hours to remove residual solvent and moisture.
[0206] After sandwiching an 18 mm diameter polyethylene diaphragm between a 14 mm diameter NCM 811 positive electrode and a 16 mm diameter graphite negative electrode, non-aqueous electrolytes from Examples 1 to 3 and Comparative Examples 1 to 6 were injected to prepare a 2032 type coin cell.
[0207] Lithium secondary batteries prepared using the non-aqueous electrolytes of Examples 1 to 3 and Comparative Examples 1 to 3 were charged and discharged 300 times at a current corresponding to 1 C within a range of 3.0 to 4.3 V to measure the discharge capacity as a function of cycles. The results are shown below. Figures 9 to 11 And in Table 3. Specifically, Figure 9 This is a graph showing the charge / discharge capacity of the lithium secondary battery prepared using the non-aqueous electrolyte of Example 2 as a function of charge / discharge. Figure 10 The graph shows the charge / discharge capacity of the lithium secondary battery prepared using the non-aqueous electrolyte of Comparative Example 1 as a function of charge / discharge. Figure 11 The graph shows the charge / discharge capacity of lithium secondary batteries prepared using non-aqueous electrolytes from Examples 1 to 3 and Comparative Examples 1 to 3 as a function of charge / discharge cycles.
[0208] Lithium secondary batteries prepared using the non-aqueous electrolytes of Examples 2 and Comparative Examples 1 and 4 to 6 were charged and discharged 200 times at a current corresponding to 1 C within the range of 3.0 to 4.3 V to measure the discharge capacity as a function of charge / discharge cycles. The results are shown in... Figure 37 middle. Figure 37 This is a graph comparing the discharge capacity of lithium secondary batteries prepared using non-aqueous electrolytes from Examples 2 and 1, 4 to 6 after 200 charge / discharge cycles.
[0209] Compared to the secondary batteries using the non-aqueous electrolytes of Comparative Examples 1 to 6, the lithium secondary batteries using the non-aqueous electrolytes of Examples 1 to 3 containing the imidazolium-based ionic liquid additive of the present invention exhibited superior lifetime characteristics. Based on these results, it can be confirmed that when the imidazolium-based ionic liquid additive of the present invention is applied in an amount of 0.2% to 3.0% by weight, a stable film is formed on the surfaces of the positive and negative electrodes through reduction and oxidation reactions, thereby exhibiting the lifetime characteristics of a lithium secondary battery.
[0210] [Table 3]
[0211] Experimental Example 3: Compositional Analysis of the Surfaces of the Negative and Positive Electrodes
[0212] X-ray photoelectron spectroscopy (XPS) surface analysis was performed to investigate the effect of the imidazolium-based ionic liquid ([FSPVI][TFSI]) additive on the electrode surface. Lithium secondary batteries prepared using the non-aqueous electrolytes of Example 2 and Comparative Example 1 were charged and discharged three times by applying a current corresponding to 0.1 C within the range of 3.0 to 4.3 V. The cells were then disassembled to analyze the differences in film composition on the negative and positive electrode surfaces.
[0213] The values were obtained from CF (688.6 eV), PF (687.6 eV), Li-F (685.5 eV), and -SO4, respectively. 2- (170.8eV), -ROSO2 - (169.5eV), -SO3 2-The XPS spectra of the graphite anode (168.3 eV), C=N (401.8 eV), and N-SO2 (400.1 eV) were deconvolved with those of the NCM cathode and the F 1s, S 2p, and N 1s XPS spectra. The XPS spectra obtained from each anode and cathode are shown in the figure. Figures 12 to 23 middle. Specifically, Figures 12 to 14 The F 1s XPS spectrum, S 2p XPS spectrum and N 1s XPS spectrum of the activated negative electrode surface of the lithium secondary battery prepared using the non-aqueous electrolyte of Example 2 are shown. Figures 15 to 17 The F 1s XPS spectrum, S 2p XPS spectrum and N1s XPS spectrum of the negative electrode surface of the lithium secondary battery prepared using the non-aqueous electrolyte of Comparative Example 1 after activation are shown. Figures 18 to 20 The F 1s XPS spectrum, S 2p XPS spectrum and N 1s XPS spectrum of the activated positive electrode surface of the lithium secondary battery prepared using the non-aqueous electrolyte of Example 2 are shown. Figures 21 to 23 The F 1s XPS, S 2p XPS, and N 1s XPS spectra of the activated positive electrode surface of the lithium secondary battery prepared using the non-aqueous electrolyte of Comparative Example 1 are shown.
[0214] Li-F (685.5 eV) possesses robust physical properties, enabling the maintenance of a stable film on the surface of the electrode active material. PF (687.6 eV) is associated with POF3 and PF5, which can be formed through electrolytic decomposition. Electrolytes containing imidazolium-based ionic liquids ([FSPVI][TFSI]) as additives exhibit a high proportion of Li-F composition and a low proportion of PF composition, indicating the formation of a stable and robust electrode surface film (SEI, CEI) that reduces electrolyte decomposition. Two peaks observed in the N 1s spectrum indicate that the electrode surface film is formed through the electrochemical decomposition of the imidazolium-based ionic liquid ([FSPVI][TFSI]).
[0215] As a result of XPS analysis, it can be confirmed that, compared with the electrode of the non-aqueous electrolyte in Comparative Example 1, the electrode of the non-aqueous electrolyte in Example 2 has an increased proportion of Li-F components that improve the physical properties of the membrane, and the lifespan and high-rate characteristics of the lithium secondary battery can be improved by forming a sulfone-based negative electrode surface film with excellent lithium-ion conductivity.
[0216] Experiment Example 4: Evaluation of High-Rate Characteristics
[0217] The lithium secondary batteries prepared using the non-aqueous electrolytes of Examples 2 and Comparative Examples 1 and 4 to 6 were each charged to 4.3 V at 25°C at a rate of 0.5 C under CC conditions, and discharged to 2.5 V at rates of 0.5 C, 1.0 C, 2.0 C, 3.0 C, and 5.0 C, respectively, which constituted one cycle. The results after 5 cycles are shown in... Figures 24 to 26 middle. Specifically, Figure 24 This is a graph comparing the discharge capacity of lithium secondary batteries prepared using the non-aqueous electrolyte solutions of Examples 2 and Comparative Examples 1 and 4 to 6 as a function of C rate; Figure 25 This is a graph showing the discharge capacity of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Example 2 as a function of C rate; Figure 26 The graph shows the discharge capacity of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 1 as a function of C rate.
[0218] like Figure 24 As shown, compared to the non-aqueous electrolytes of Comparative Examples 1 and 4 to 6, the lithium secondary battery using the non-aqueous electrolyte of Example 2, which contains an imidazolium-based ionic liquid ([FSPVI][TFSI]) additive, exhibits superior performance in terms of high-rate characteristics above 2.0 C. These results confirm that when the imidazolium-based ionic liquid ([FSPVI][TFSI]) additive of the present invention is applied to the electrolyte, a stable film with excellent lithium-ion conductivity can be formed on the electrode surface through reduction and oxidation reactions.
[0219] Experiment Example 5: Confirmation of Interface Resistance Change
[0220] Electrochemical impedance spectroscopy (EIS) was performed to determine the change in interfacial resistance of the lithium secondary battery with the addition of an imidazolium-based ionic liquid ([FSPVI][TFSI]). Typically, the semicircles observed at high frequencies represent the film resistance (Rt) formed on the electrode surface. f The semicircle observed in the mid-frequency region represents the resistance (R0) of the charge transfer reaction at the electrode surface. ct ). Figure 27 This is a graph showing the change in interfacial resistance during the first cycle of lithium secondary batteries prepared using the non-aqueous electrolyte solutions of Example 2 and Comparative Example 1. Figure 28 This is a graph showing the change in interfacial resistance during the 300th cycle of lithium secondary batteries prepared using the non-aqueous electrolyte solutions of Example 2 and Comparative Example 1.
[0221] like Figure 27 and Figure 28As shown, compared to the lithium secondary battery using the non-aqueous electrolyte of Comparative Example 1, the lithium secondary battery using the non-aqueous electrolyte of Example 2 (in which 0.5% by weight of an imidazolium-based ionic liquid ([FSPVI][TFSI]) additive) exhibited a lower increase in interfacial resistance after 300 cycles. These results demonstrate that when the imidazolium-based ionic liquid ([FSPVI][TFSI]) additive of the present invention is applied to the electrolyte, a stable and robust SEI and CEI layer is formed on the electrode surface, which improves lithium mobility and prevents side reactions between the electrode and the electrolyte, thereby suppressing the increase in cell impedance.
[0222] Experimental Example 6: Morphology (SEM) of the negative and positive electrode active materials after cycling
[0223] Scanning electron microscope (SEM) images of the graphite anode and NCM 811 cathode of the non-aqueous electrolyte prepared in Example 2 and Comparative Example 1 are shown in Figures 29 to 36 middle. Specifically, Figure 29 and Figure 30 SEM images of the graphite anode of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 1 before and after 300 charge / discharge cycles. Figure 31 and Figure 32 The images are SEM images of the graphite anode of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Example 2 before and after 300 charge / discharge cycles. Figure 33 and Figure 34 SEM images of the NCM cathode of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Comparative Example 1 before and after 300 charge / discharge cycles. Figure 35 and Figure 36 These are SEM images of the NCM cathode of the lithium secondary battery prepared using the non-aqueous electrolyte solution of Example 2 before and after 300 charge / discharge cycles.
[0224] from Figure 29 , 30 As can be seen from 33 and 34, cracks were observed on the graphite anode and NCM 811 cathode surfaces of the lithium secondary battery using the non-aqueous electrolyte of Comparative Example 1 after repeated charge / discharge cycles, indicating that the electrode surface film cannot serve as a robust protective layer. Conversely, in Figure 31 , 32 As confirmed in 35 and 36, the lithium secondary battery using the non-aqueous electrolyte of Example 2 exhibited reduced cracking on the electrode surface. These results confirm that the imidazolium-based ionic liquid ([FSPVI][TFSI]) additive can decompose on the electrode surface to participate in the formation of stable SEI and CEI layers, thereby preventing side reactions between the electrode and the electrolyte.
Claims
1. A non-aqueous electrolyte comprising: Lithium salts; Organic solvents; and additive, in, The additives include compounds represented by Formula 1: [Formula 1] In Formula 1, R1 is an alkenyl group having 2 to 5 carbon atoms, R2 to R4 are each independently fluorine or alkyl groups having 1 to 10 carbon atoms substituted with one or more fluorine atoms, and L1 is an alkylene group having 1 to 10 carbon atoms or an aryl group having 6 to 20 carbon atoms.
2. The non-aqueous electrolyte as described in claim 1, in, R1 is an alkenyl group having 2 to 4 carbon atoms.
3. The non-aqueous electrolyte as described in claim 1, in, R1 is vinyl.
4. The non-aqueous electrolyte as described in claim 1, in, R2 to R4 are alkyl groups having 1 to 6 carbon atoms that have been substituted with one or more fluorine molecules.
5. The non-aqueous electrolyte as described in claim 1, in, R2 to R4 are alkyl groups having 1 to 4 carbon atoms that have been substituted with one or more fluorine molecules.
6. The non-aqueous electrolyte as described in claim 1, in, R2 is fluorine.
7. The non-aqueous electrolyte as described in claim 1, in, R3 and R4 are each trifluoromethyl.
8. The non-aqueous electrolyte as described in claim 1, in, L1 is an alkylene group having 1 to 5 carbon atoms or an aryl group having 6 to 20 carbon atoms.
9. The non-aqueous electrolyte as described in claim 1, in, L1 is an alkylene group having 1 to 3 carbon atoms or an aryl group having 6 to 10 carbon atoms.
10. The non-aqueous electrolyte as described in claim 1, in, R1 is any one of the groups consisting of substituents represented by formulas R1-1, R1-2, and R1-3: [Equation R1-1] [Equation R1-2] [Equation R1-3] 。 11. The non-aqueous electrolyte as described in claim 1, in, The compounds represented by Formula 1 include those represented by Formula 1-1: [Equation 1-1] 。 12. The non-aqueous electrolyte as described in claim 1, in, The content of the additive in the non-aqueous electrolyte is from 0.15% to 10% by weight.
13. The non-aqueous electrolyte as described in claim 1, in, The lithium salt is selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium perchlorate, lithium bis(oxalate)borate, and mixtures of two or more thereof.
14. The non-aqueous electrolyte as described in claim 1, in, The concentration of the lithium salt contained is from 0.5 M to 5.0 M.
15. The non-aqueous electrolyte as described in claim 1, in, The organic solvent includes at least one selected from cyclic carbonate organic solvents, linear carbonate organic solvents, linear ester organic solvents, and cyclic ester organic solvents.
16. A lithium secondary battery, comprising: negative electrode; The positive electrode opposite to the negative electrode; A diaphragm is disposed between the negative electrode and the positive electrode; and The non-aqueous electrolyte according to claim 1.
Citation Information
Patent Citations
plaque stands set up for advertising purposes
CH32222A